2005
DOI: 10.1007/bf02893064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ocimum flavonoids as a radioprotector on the erythrocyte antioxidants in oral cancer

Abstract: Flavonoids extracted from the leaves of Indian holy basil, Ocimum sanctum showed promising results as radioprotector in rodents. Hence it was thought pertinent to analyze the antioxidants of erythrocytes in oral cancer patients who were concurrently treated with radiation and ocimum flavonoids. Oral cancer patients consisted of 2 groups. Group A(n=17) received radiation alone while Group B(n=17) received radiation and ocimum flavonoids(OF). Samples of heparinised blood were collected prior to treatment, 15 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Because of their low toxicity, botanical and natural products have been evaluated for their radioprotective potentials. Plants containing polyphenolic compounds ( 34,35) , Naringenin (36) , -lavonoids of Rosa roxburghii Tratt (37) , ocimum -lavonoids (38,39) have shown antioxidative activities and protect genetic material from ionizing radiation. Radioprotective effect of all tested herbal products were attributed to their antioxidant properties.…”
Section: Imod (Mg/kg)mentioning
confidence: 99%
“…Because of their low toxicity, botanical and natural products have been evaluated for their radioprotective potentials. Plants containing polyphenolic compounds ( 34,35) , Naringenin (36) , -lavonoids of Rosa roxburghii Tratt (37) , ocimum -lavonoids (38,39) have shown antioxidative activities and protect genetic material from ionizing radiation. Radioprotective effect of all tested herbal products were attributed to their antioxidant properties.…”
Section: Imod (Mg/kg)mentioning
confidence: 99%
“…The inoculation of bio-fertilizer like Rhizobium increases the number of such microorganisms in the soil rhizosphere and consequently improves the extent of microbiologically fixed nitrogen for plant growth (Saxena and Singh, 2019). The inoculation of AM fungi in soil also helped in enhancing the plant growth thereby resulting into early flowering (Sharma et al, 2005). The effect of seed inoculation with Rhizobium increased number of branches and showed a significant and positive result in improving nitrogen nutrient contents of plant (Malav et al, 2018).…”
Section: Emergence and Growth Parametersmentioning
confidence: 99%
“…In addition, the administration of flavonoids to mice treated with radiation results in increased antioxidant enzyme activity and decreased lipid peroxidation by the scavenging of hydroxy radicals [78]. Reshma et al [79] examined the effect of flavonoids on erythrocyte antioxidant defence potential in oral and oropharyngeal cancer patients and showed that erythrocytes from cancer patients responded to oxidative stress by increasing glutathione levels, whilst a decrease in glutathione levels was observed in the group receiving both radiotherapy and ocimum flavonoids.…”
Section: Flavonoidsmentioning
confidence: 99%